Targeted sequencing of candidate gene regions for myelofibrosis in dogs. (11th July 2022) - Campbell, Amelia G.; Seelig, Davis M.; Beckman, Joan D.; Minor, Katie M.; Heinrich, Daniel A.; Friedenberg, Steven G.; Modiano, Jaime F.; Furrow, Eva
Abstract: Background: Myelofibrosis often lacks an identifiable cause in dogs. In humans, most primary myelofibrosis cases develop secondary to driver mutations in JAK2, CALR, or MPL . Objectives: To determine the prevalence of variants in JAK2, CALR, or MPL candidate regions in dogs with myelofibrosis and in healthy dogs. Animals: Twenty‐six dogs with myelofibrosis that underwent bone marrow biopsy between 2010 and 2018 and 25 control dogs matched for age, sex, and breed. Methods: Cross‐sectional study. Amplicon sequencing of JAK2 exons 12 and 14, CALR exon 9, and MPL exon 10 was performed on formalin‐fixed, decalcified, paraffin‐embedded bone marrow (myelofibrosis) or peripheral blood (control) DNA. Somatic variants were categorized as likely‐benign or possibly‐pathogenic based on predicted impact on protein function. Within the myelofibrosis group, hematologic variables and survival were compared by variant status (none, likely‐benign only, and ≥1 possibly‐pathogenic). The effect of age on variant count was analyzed using linear regression. Results: Eighteen of 26 (69%) myelofibrosis cases had somatic variants, including 9 classified as possibly‐pathogenic. No somatic variants were detected in controls. Within the myelofibrosis group, hematologic variables and survival did not differ by variant status. The number of somatic variants per myelofibrosis case increased with age (estimate, 0.69; SE, 0.29; P  = .03). Conclusions and Clinical Importance: Somatic variants might initiate or perpetuate myelofibrosis in dogs. Our findings suggest the occurrence of clonal hematopoiesis in dogs, with increasing incidence with age, as observed in humans.